Maternal and Perinatal Outcomes in Childbirths with Meconium Stained Amniotic Fluid in a Low-resource Setting: A Prospective Cohort Study - Gregory E. Halle-Ekane; Phyllis N. Fon; Paul N. Koki; Alexis A. Tazinya; Rodrigue Ekollo; Emile Mboudou (Archives of Current Research International, 2019)
Meconium stained amniotic fluid (MSAF) can be associated with a high maternal and perinatal mortality. There is paucity of data on maternal and fetal outcomes of MSAF in Cameroon. Aim: The study was to determine the maternal and perinatal outcomes in patients with MSAF. Study Design: Prospective cohort study. Place and Duration of Study: The study carried out in the Limbe Regional Hospital maternity, Cameroon from 10th January 2017 to 20th April 2017. Methodology: Fifty- two mothers who had MSAF and their neonates, were matched with controls (without MSAF) in a 1:1 ratio after matching for: age, gestational age, parity and body mass index. Risk ratio (RR) of MSAF on the various perinatal outcomes were calculated by multivariate logistic regression with MSAF (-) being the reference. Data was analyzed with Epi Info 7. Results: Two hundred and three deliveries were conducted during the study period with fifty-two with MSAF enrolled in the study. The proportion of participants with MSAF was 19.1%. Parturients who had thick MSAF were 3 times more likely to have caesarean sections (RR: 3.2, 95% CI= 1.1 - 10.2, p = 0.04). Two (3.9%) parturients with chorioamnionitis had MSAF. The neonatal complications were: non- reassuring fetal heart rate (RR=4.4, 95%CI: 1.1-16.8, p=0.02), neonatal sepsis (RR=3.7, 95%CI: 1.4-9.8, p=0.01) and neonatal intensive care unit admissions (RR=2.9, 95%CI: 1.2-6.9, p=0.02), were associated with MSAF. Two (3.9%) had meconium aspiration syndrome on clinical examination. No maternal death was recorded. However, a perinatal death occurred in a parturient with MSAF. Conclusion: The proportion of parturients with MSAF was high. MSAF was associated with increased maternal and neonatal morbidity. We recommend larger and robust cohort studies to further refine our findings.